Organotypic Bone Culture: An In Vitro Model for the Development of Mature Bone Containing an Osteocyte Network (Adv. Biosys. 2/2018). Issue 2 (13th February 2018) - Iordachescu, Alexandra; Amin, Harsh D.; Rankin, Sara M.; Williams, Richard L.; Yapp, Clarence; Bannerman, Alistair; Pacureanu, Alexandra; Addison, Owen; Hulley, Philippa A.; Grover, Liam M.
Abstract : In article number1700156 by Alexandra Iordachescu and co‐workers, a newly developed organotypic bone‐culture system allows the differentiation of encapsulated osteoprogenitor cells into mature bone cells, the osteocytes, and the generation of a microenvironment similar to their endogenous matrix, thus permitting the maintenance of this phenotype over extended culture periods. This scanning‐electron‐microscopy image acquired from a bone‐like construct after 12 months of culture shows osteocytic cells embedded in a significantly mineralized matrix, which communicate through numerous projections characteristic to this cell type. Cover art prepared by Alexandra Iordachescu.